Production and characterisation of spray dried particulate systems for pulmonary drug delivery - Gad, Shadeed (Trinity College (Dublin, Ireland). School of Pharmacy & Pharmaceutical Sciences, 2009)
The work presented in this thesis concerns the application of a particle engineering technology, one-step spray drying method, to produce porous particles of antitubercular drugs, suitable for inhalation and to study the effect of spray drying on acidic model drugs and their ammonium salts. Five antitubercular drugs in addition to four acidic model drugs and their ammonium salts were selected for analysis. The spray drying process employed involved the spray drying of a solution of drug or excipient with or without a pore-forming agent (for example ammonium carbonate) to produce the desired nanoporous microparticles (NPMPs). Recovered particles were visualised by scanning electron microscopy. The physicochemical characteristics of the unprocessed and spray dried samples were compared in terms of solid-state characterisation; thermal behaviour, residual solvent content, powder x-ray diffraction and Fourier Transform Infrared Spectroscopy. Elemental analysis, nuclear magnetic resonance and HPLC were carried out for selected samples to evaluate the chemical structure of certain spray dried samples. Micromeritic characteristics of selected systems were investigated. These included evaluation of specific surface area, particle size, bulk and tapped densities. In-vitro deposition of powders was evaluated.
Keywords: Pharmaceutics, Ph.D.; Ph.D. Trinity College Dublin